The effect of child labor in engaging learning at classroom situation: a case study from a primary school in urban Dhaka - Jahan, Israt (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Masters of Science in Early Child Development, 2021.